RANCANG BANGUN SISTEM ELEVATOR MINI BERBASIS DUAL ARDUINO DENGAN KOMUNIKASI I2C - Ilham Rizky Ananda; Manuel Manuel; Ergy Firly; Eka Dodi Suryanto; Dian Putra Saragi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study is motivated by the limitations of systems that can represent the working principles of elevators in a practical and applicative manner within the field of control systems. The purpose of this research is to design and develop a mini elevator prototype based on two Arduino Uno microcontrollers communicating via the Inter-Integrated Circuit (I2C) protocol. The method used is experimental research with a system engineering approach, including system design, assembly, programming, and testing stages. The proposed system consists of a master Arduino as the main controller and a slave Arduino for controlling the automatic door system and sensors. The main components include a DC motor as the driving system, limit switches as position sensors, an ultrasonic sensor for safety detection, and a servo motor for the automatic door mechanism. The test results show that the system is capable of responding quickly to button inputs, accurately stopping the motor based on limit switch signals, and operating the automatic door system effectively. Furthermore, I2C communication between the two microcontrollers runs stably and in real-time. Therefore, the proposed prototype successfully implements a closed-loop control system and can serve as a reference for the development of microcontroller-based control systems.